ПОДХОД К ПРОБЛЕМЕ СОЦИАЛИЗАЦИИ В РАЗЛИЧНЫХ ПСИХОЛОГИЧЕСКИХ НАПРАВЛЕНИЯХ - Тлеумбетова, К.Д. (SCIENCE and SOCIETY, 2024)
This article outlines the theories of foreign psychologists about the problems of the process of socialization of a child into society, as well as the factors influencing the development of a child’s personality.
Keywords: socialization; self-awareness; personality; formation; factors; communication